The Effect of Product Promotion and Innovation Activities on Marketing Performance in Middle Small Micro Enterprises in Cianjur - Nurjaya Nurjaya; Azhar Affandi; Heri Erlangga; Denok Sunarsi; Jasmani Jasmani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of promotional activities and product innovation on marketing performance in Micro, Small and Medium Enterprises in Cianjur. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that promotional activities have a significant effect on marketing performance by 40.0%, hypothesis testing is obtained t count> t table or (7.915> 1.986). Product innovation has a significant effect on marketing performance by 38.5%, the hypothesis test obtained t count> t table or (7,669> 1,986). Promotional activities and product innovation simultaneously have a significant effect on marketing performance with the regression equation Y = 11.022 + 0.374X1 + 0.360X2. Contribution of influence is 49.3%, hypothesis testing obtained F count> F table or (45,302> 2,700).